Screening of Biosurfactants from Hydrocarbon Degrading Bacteria - C. Chellaram2, T. Prem Anand2,; V. Kannan1, R. Nishanthi1*, S. Kumaran2, P. Palani1, (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Biosurfactants compounds are produced by microorganisms. These isolates reduced surface tension both in aqueous solutions and hydrocarbon mixtures. The objective of this study was to isolate and identify the biosurfactant producing bacteria from petrochemical soil wastes. Among the 16 isolates, two strains (BPB7: Pseudomonas sp and BPB13: Serratia sp) were shown high salt tolerance and successful production of biosurfactant in a range of pH 6.5 to 7.5 and at room temperature. To confirm the ability of isolates in biosurfactant production, different screening methods including hemolysis, emulsification, penetration, oil spreading test BATH assay and salt aggregation assay were assessed. This study was suggested that these two bacteria having potential for microbial enhanced oil recovery and also possessing Anti microbial and Anti adhesive property. The rich amount of biosurfactant compound like, glycolipid was found in these two strains. (BPB7 and BPB13).